PENERAPAN ARSITEKTUR EKOLOGIS PADA RANCANGAN BALAI PENELITIAN DAN PENGEMBANGAN HORTIKULTURA DI GORONTALO - Bayu, Bayu Setiawan; Pratiwi, Niniek; Ernawati, Ernawati (Program Vokasi Universitas Negeri Gorontalo, 2024)
ABSTRACT. Horticulture is one of the agricultural sectors that has considerable potential in advancing the economy in Indonesia. The lack of adequate support and facilities from local governments and related institutions in developing the agricultural sector is one of the factors affecting the limited development of the horticulture sector in Gorontalo Province. Therefore, to accommodate research activities and development of horticultural crops, it is necessary to design a horticultural research and development center. Horticultural research and development center, is a place designed to produce and develop horticultural innovations based on local resources and sustainable while maintaining balance and environmental sustainability. The purpose of designing this building is to provide a place that can facilitate horticultural research and development activities and also to apply an ecological architectural approach to the design of horticula research and development centers by considering the interrelationships between humans and the surrounding environment. The application of ecological architecture is applied to building facades such as the application of sun shading on the exterior of buildings, the use of environmentally friendly materials, and the shape of the façade will be arranged as well as possible so that sunlight can be transmitted evenly into the building. In addition, on the roof of the building will also be placed solar panels which are a natural source of energy in the building. It is hoped that the design of this building can facilitate all horticultural research and development activities in Gorontalo.Keywords: Balitbang, Horticulture, Ecological ArchitectureABSTRAK. Hortikultura merupakan salah satu sektor pertanian yang memiliki potensi cukup besar dalam memajukan perekonomian di Indonesia. Kurangnya dukungan dan fasilitas yang memadai dari pemerintah daerah dan lembaga terkait dalam mengembangkan sektor pertanian adalah salah satu faktor yang mempengaruhi terbatasnya perkembangan sektor hortikultura di Provinsi Gorontalo. Oleh sebab itu untuk mewadahi aktivitas penelitian serta pengembangan tanaman hortikultura, maka perlu untuk dirancang sebuah balai penelitian dan pengembangan hortikultura. Balai penelitian dan pengembangan hortikultura, adalah tempat yang dirancang guna menghasilkan dan mengembangkan inovasi hortikultura yang berbasis sumber daya lokal serta berkelanjutan dengan tetap menjaga keseimbangan serta kelestarian lingkungan. Tujuan perancangan gedung ini adalah untuk menyediakan tempat yang dapat memfasilitasi kegiatan penelitian dan pengembangan hortikultura dan juga untuk menerapkan pendekatan arsitektur ekologis pada perancangan balai penelitian dan pengembangan hortikulutra dengan mempertimbangkan hubungan timbal balik antara manusia dengan lingkungan sekitarnya. Penerapan arsitektur ekologis diterapkan pada fasad bangunan seperti penerapan sun shading pada eksterior bangunan, penggunaan material yang ramah lingkungan, serta bentuk fasadnya akan ditata sebaik mungkin agar cahaya matahari dapat diteruskan secara merata ke dalam bangunan. Selain itu, pada atap bangunan juga akan diletakkan panel surya yang menjadi sumber energi alami pada bangunan. Diharapkan dengan adanya perancangan gedung ini dapat memfasilitasi seluruh kegiatan penelitian dan pengembangan hortikultura yang ada di Gorontalo. Kata Kunci: BALITBANG, Hortikultura, Arsitektur Ekologis